Perilaku Pembelian Impulsif : Seberapa Besar Peran Gaya Hidup dan Literasi Ekonomi ? - Desi Choirunnisa (Jurnal Pendidikan Ekonomi, 2021)
The pattern of consumption of buying expensive goods is the lifestyle of adolescents at this time. Students as consumption agents have been provided with literacy and have behaved impulsively in purchasing.  This objective of study was to analyze the effect of Economic Literacy on Lifestyles, the effect of Economic Literacy on Impulsive Buying Behavior, the influence of Lifestyle on Impulsive Buying Behavior, and the influence of Economic Literacy through Lifestyle on Impulsive Buying Behavior of fashion products I online shops. This research is a type of quantitative research. The subject of study was students of The Faculty of Economics at the State University of Surabaya, who had just finished taking the microeconomic theory course. The study involved 162 students. The data collection technique using questionnaires and tests were analyzed with structural equation modeling (SEM) analysis techniques. The results of this study are economic literacy has a significant effect on lifestyles, economic literacy has a significant effect on impulsive buying behavior, lifestyle have a significant impact on impulsive buying behavior, and economic literacy has a significant effect on impulsive buying behavior through lifestyle so that lifestyle is mediating variable. Based on the assessment of the results of the study, students are accustomed to applying in their lifestyles ie students product because of trends but do not neglect the benefits of the products. Because of that habit students also apply economic literacy to the impulsive buying behavior of fashion products in the online shop.DOI: https://dx.doi.org/10.17977/UM014v14i12021p61